2022
DOI: 10.1002/cphc.202200394
|View full text |Cite
|
Sign up to set email alerts
|

“Cap‐Pair” Effect as the Reason of the Catalytic Properties of Nicotinic Acid: Experimental and Theoretical Studies

Abstract: The influence of nicotinic acid (NC) on the kinetics and the mechanism of electroreduction of Zn2+ ions in the acetate buffer (pH=6.0) was investigated using electrochemical methods (EIS, CV, SWV and DC). It was shown that the anions of NC catalyze the electrode reaction (cap‐pair effect) by adsorbing on the surface of the mercury electrode. The catalytic activity of NC is due to its ability to form active NC−Zn2+ complexes on the electrode surface, facilitating the electron transfer process. However, no evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The number of water molecules in the In(III) hydration sphere is larger than in the case of In(II) or In(I) ion. It has been demonstrated that the adsorption of organic molecules increases due to the higher concentration of ClO 4 − ions which causes smaller hydration of a near‐electrode surface [19] . The competitive adsorption of acetazolamide, water and to a small extent, ClO 4 − in the double layer interface should be considered [25] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of water molecules in the In(III) hydration sphere is larger than in the case of In(II) or In(I) ion. It has been demonstrated that the adsorption of organic molecules increases due to the higher concentration of ClO 4 − ions which causes smaller hydration of a near‐electrode surface [19] . The competitive adsorption of acetazolamide, water and to a small extent, ClO 4 − in the double layer interface should be considered [25] .…”
Section: Resultsmentioning
confidence: 99%
“…As the concentration of the base electrolyte increases, the slope of the DC polarographic curves of the electroreduction of In(III) ions varies, confirming changes in the reversibility of the electrode process. [18,19] It should be also noted that in solutions with higher chlorates(VII) concentrations there is a significant increase in the limiting current and the waves become better defined. Such fluctuations in the limiting current are the evidence of changes in the viscosity of the base electrolyte solution.…”
Section: Polarographic and Voltammetric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation